Chronic alcohol intake disrupts cytochrome P450 enzyme activity in alcoholic fatty liver disease: insights into metabolic alterations and therapeutic targets - Zhu, Qian; Xie, Xuefeng; Fang, Ling; Huang, Cheng; Li, Jun (Frontiers in Chemistry, 2025)
IntroductionAlcoholic fatty liver disease (AFLD) is a common consequence of chronic alcohol consumption, characterized by lipid accumulation and oxidative stress in the liver. Cytochrome P450 (CYP450) enzymes play essential roles in metabolizing alcohol and other compounds. However, the specific long-term effects of alcohol on these enzymes remain unclear.MethodsThis study the examines influence of prolonged ethanol exposure on CYP450 activity and expression in AFLD using a rat model. Key enzymes such as CYP2E1, CYP2D6, and CYP3A1 were assessed in relation to lipid accumulation and oxidative stress.ResultsSignificant alterations were identified in the expression and activity of CYP2E1, CYP2D6, and CYP3A1, which were associated with increased lipid accumulation and oxidative stress in the liver. Additionally, the expression of P-glycoprotein (P-gp) was elevated, suggesting that chronic alcohol intake may impact drug transport and excretion.DiscussionThese findings provide new insights into the molecular mechanisms of AFLD and highlight the potential of CYP450 modulation as a therapeutic target. By elucidating how long-term ethanol exposure disrupts hepatic CYP450 enzyme profiles, this research lays the groundwork for developing personalized therapeutic strategies to improve outcomes for patients with AFLD.